2004
DOI: 10.1620/tjem.202.77
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Flow Velocity and Coronary Flow Velocity Reserve in Children with Ventricular Septal Defect

Abstract: HARADA, K., AOKI, M., TOYONO, M. and TAMURA, M. Coronary Flow Velocity and Coronary Flow Velocity Reserve in Children with Ventricular Septal Defect. Tohoku J. Exp. Med., 2004, 202 (2), 77-85 To assess coronary flow characteristics in congenital heart defect with left ventricular (LV) volume overload, we examined 24 children (mean 12.1±7.1 months) with ventricular septal defect. The pulmonary to systemic flow ratio ranged from 1.1 to 3.0. Control group consisted of 10 age-matched children who had a history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Because there is a certain maximal dilatory state that can be reached, it is conceivable to assume that an increase in CF may lead to impaired CFR (38). Therefore, our findings support earlier studies by positron emission tomography (PET) and intracoronary Doppler guide wire (IDGW) showing a drop in CFR after CBP surgery (7,13). In contrast, surgical off-pump correction of aortic coarctation resulted in decrease of both myocardial oxygen consumption and coronary flow, which implies either that off-pump surgery has little or no effect on the coronary flow or that the removal of pressure overload after coarctectomy counteracts possible detrimental effects of off-pump surgery on coronary flow.…”
Section: Discussionsupporting
confidence: 91%
“…Because there is a certain maximal dilatory state that can be reached, it is conceivable to assume that an increase in CF may lead to impaired CFR (38). Therefore, our findings support earlier studies by positron emission tomography (PET) and intracoronary Doppler guide wire (IDGW) showing a drop in CFR after CBP surgery (7,13). In contrast, surgical off-pump correction of aortic coarctation resulted in decrease of both myocardial oxygen consumption and coronary flow, which implies either that off-pump surgery has little or no effect on the coronary flow or that the removal of pressure overload after coarctectomy counteracts possible detrimental effects of off-pump surgery on coronary flow.…”
Section: Discussionsupporting
confidence: 91%
“…15,23,24 Coronary flow reserve in a variety of congenital cardiac lesions (VSD, TGA, tetralogy of Fallot, hypoplastic left heart syndrome) is lower than in adults. [25][26][27][28][29] These findings are similar to ours, where the CFR in all groups was <2.2. The lower CFR may be due to the observed higher basal coronary flow with a more blunted hyperaemic response.…”
Section: >90%supporting
confidence: 89%
“…Positron emission tomography technique has shown it to be decreased 1-3 weeks after surgery on CPB [2]. Intracoronary Doppler flow guide wire (IDGW) studies done 5-7 months after surgery showed improved but still low CFR as compared to presurgical values [7].…”
Section: Introductionmentioning
confidence: 99%